Marketing issues of sustainable tourism development in Russian regions - Marina Y. Sheresheva; Anna N. Polukhina; Matvey S. Oborin (Journal of Tourism, Heritage & Services Marketing, 2020)
This paper aims to provide a better understanding of marketing issues relevant to sustainable tourism development. Marketing issues are of crucial importance for Russian regions with unique landscapes and many small towns with their ancient churches, original local museums, and other attractions. The main obstacle for sustainable tourism development in these regions is the lack of prominence and absence of right positioning for target audiences. For the Mari El Republic as one of the most prospective sustainable tourism destinations in Russia, ethno-tourism concept, based on preserving paganism, the traditional religion of the Mari people, can become a solid basis for positioning. The research presented in the paper will contribute to the literature on tourism marketing and sustainable regional development in emerging markets by shedding light on the Russian tourism market diversity, as well as on the uniqueness of small Russian towns and villages as attractive destinations in terms of cultural heritage, history, and ecology. It will also underline the need to understand socio-cultural specifics of tourism destinations to ensure positive impact on the prosperity of local communities that are among the most important stakeholders in destination marketing.
Keywords: M31; Q01; Z32; 330; Tourism; marketing; sustainable tourism; small settlements; destination development; Russia